Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Can someone solve this using completing the square method? MATH problem?
Help me solve this using "Completing The Square Method"
X²+5X+4=0
If you dont know how to put the radical sign, just copy paste the radical sign below:
√
Thank You So Much :)
God Bless \m/
5 Answers
- I'm with StupidLv 71 decade agoFavorite Answer
x² + 5x + 4 = 0
x² + 5x = -4
x² + 5x + (2.5)² = 2.25
(x + 2.5)² = 2.25
x + 2.5 = ±√(2.25)
x = -2.5±1.5
x = -1 or x = -4
♣♦
- AeroLv 61 decade ago
Here we go:
x² + 5x + 4 = 0
x² + 5x = -4²
x² + 5x + (5/2)² = -4 + (5/2)²
(x + (5/2) )² = 9/4
As a decimal:
x² + 5x + (2.5)² = -4 + (2.5)²
(x + 2.5)² = 2.25
x + 2.5 = â2.25
x = â2.25 - 2.5
x = plus or minus 1.5 - 2.5
x either = -4 or -1
Check your answer buy putting -4 and -1 into the original x² + 5x + 4 = 0 equation.
Hope this helps, as it can be a bit hard to understand via typing.
- 1 decade ago
X²+5X+4=0, subtract 4 on both sides, or simply transpose 4 to the right side
X²+5X + 4-4=0 - 4
X²+5X = -4, we know that 5X is twice the product of the 1st and 2nd term i.e. 5X = 2(X)(?), ? = 5/2
So:
(X + 5/2)^2 = -4 + (5/2)^2
then take â
of both sides,
X + 5/2 = + or minus sqrt[-4 + 25/4] = sqrt [(-16 + 25)/4] = 3/2
the X = -(5/2) + 3/2 = -1
or X = -(5/2) - 3/2 = -4
Please recheck especially algebraic signs.
Cheers!
Source(s): KnowledgeBank - YoyoLv 41 decade ago
a=1 b=5 c=4
x²+5x=-4
x²+5x+(b/2)² = -4 + (b/2)²
x²+5x+6.25 = -4+6.25
x²+5x+6.25 = 2.25
(x+2.5)²=2.25 =====> (x+2.5)² came from factoring x²+5x+6.25 because 2.5+2.5 = 5 and 2.5 x 2.5 = 6.25
x+2.5=â2.25
x = -2.5 + or - â2.25 By + or -, I mean plus on top of the minus... You know what I mean.
x1=-2.5+1.5 = -1
x2 = -2.5 - 1.5 = -4
x = -1, -4
Source(s): Good luck :D - 1 decade ago
Okay basically for completing the square method, you have to use (a-x)^2+b.
Then expand it.
Therefore you should get X²+5X+4= x^2-2ax+a^2+b
Next, compare the equation.
5x=-2ax
a=5/2
=2.5
(2.5)^2+b=4.
b= -2.25
Therefore X²+5X+4=(2.5-x)^2-2.25
Hope I helped
Source(s): 'A' in maths